EXTENSIVELY DRUG-RESISTANT ENTERIC FEVER IN CHILDREN: SURGING THREATS OF ANTIMICROBIAL RESISTANCE AND POSSIBLE SOLUTIONS - Bibi, Saima; Gilani, Syed Yasir Hussain; Siddiqui, Tahir Saeed; Syed, Fibhaa; Arif, Mohammad Ali; Haider, Nighat (Journal of Ayub Medical College Abbottabad, 2023)
Background: Enteric fever is an infectious disease caused by Salmonella enterica including Salmonella Typhi and Paratyphi A and is associated with potentially serious outcomes, especially in developing countries. The study was conducted with the aim to present the clinical features, laboratory characteristics and antibiotic susceptibility in patients with culture-proven extensively drug-resistant (XDR) enteric fever and to explore drug combinations as a possible solution for the growing problem of antimicrobial resistance. Methods: This descriptive cross-sectional study was conducted in the Paediatric unit of Ayub teaching hospital. Patients admitted with culture-proven XDR enteric fever were included. Patient characteristics were documented on a predesigned proforma. Response to antimicrobial agents including ceftriaxone and levofloxacin, azithromycin and meropenem and meropenem alone was assessed. Data was entered and analyzed using SPSS version 26. Results: A total of 53 patients participated in this study. The majority of patients 36 (67.9%) were male and above 5 years of age(n=38,71.7%). The mean age of the participants was 7.08±3.02 years. The major presenting features included fever, anorexia and pain abdomen in 53 (100%), 51 (96.2%) and 41 (77.4%) respectively. The mean duration of symptoms prior to hospitalization was 8.92±3.361 days. Of the total patients, 32(60.4%) responded to the initial therapy with ceftriaxone and levofloxacin, 11(20.8%) patients responded to meropenem alone and 10 (18.9%) patients responded to meropenem and azithromycin in combination. There was no statistically significant difference in mean duration to show response in patients receiving either of the treatments (p=0.484). Conclusion: Paediatric patients with XDR enteric fever mainly presented with fever, anorexia and pain abdomen and showed good response to therapy with the combination of ceftriaxone and levofloxacin inspite of the apparent resistance on blood culture and sensitivity